THE EFFECTIVENESS OF SMART BOOK MEDIA ON THE INTRODUCTION OF SEX EDUCATION IN GROUP B1 CHILDREN AT IK NURUL QUR'AN KINDERGARTEN GREAT ACEH - Liza Fidiawati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Introducing sex education to early childhood involves providing an understanding of their body, recognizing the opposite gender, and learning how to protect themselves from sexual abuse, thereby mitigating the occurrence of sexual violence and criminal acts. This research aimed to determine the effectiveness of the Smart Book media in introducing sex education to Group B1 children at TK IK Nurul Qur'an, Aceh Besar. The study employed a quantitative method with a one-group pre-test and post-test experimental design. A sample of 16 children was observed, and data were analyzed statistically. The results revealed that the Smart Book media effectively enhanced children's understanding of sex education, as evidenced by an increase in the average pre-test score (9) to the post-test score (13.5). Statistical hypothesis testing indicated significant effectiveness, with a calculated t-value of -18.933 and a significance value ≤ 0.01 (df = 15, t-table = 1.753). Thus, the hypothesis was accepted, indicating significant effectiveness of Smart Book media in improving sex education comprehension among 5-6-year-old children.